Gender-Neutral Pathways to Positive Behavior: Investigating the Role of Self-Actualisation and Academic Achievement in Secondary Education - Gamal Abdul Nasir Zakaria; Desfa Yusmaliana; Zaimah Hj Abdullah; Mussa Saidi Abubakari; Ibrahem Narongrakshakhet; Barot Amonov (Universitas Muhammadiyah Surakarta, 2025)
Self-actualisation and positive behaviour play a principal role in life, especially among students, enabling them to overcome challenges. This study aimed to explore the comparison of self-actualisation between genders and the relationship between self-actualisation scores and academic achievement in producing positive behaviour. A total of 259 secondary-level students, comprising 125 males and 134 females, participated in this quantitative study. Questionnaires were distributed to collect data, and correlation and t-test analyses were conducted. The findings indicated that there was no significant difference in self-actualisation between genders and academic achievement in producing positive behaviour. This indicates that the self-development programs and psychological interventions in schools are important for creating an environment that supports personal growth without gender bias. Similarly, the lack of a significant difference between academic achievement and self-actualization suggests that academic factors are not the only ones influencing students' positive behavior. Instead, other elements, such as emotional support, social involvement, and extracurricular experiences, may play a greater role in shaping students' behavior.